Decompensated heart failure patients: there are simple parameters that could be integrated in a machine learning process to improve our strategies - Donal, Erwan (Journal of Laboratory and Precision Medicine, 2017)
Heart failure (HF) remains an extremely severe disease despite pharmacological innovation (1) as well as devices that are largely used. Still HF is a diagnosis associated with a mortality greater than most cancers (2). A large effort is thus, still, required to define best the strategies and the individualized managements that are supposed to improve the prognostic of the disease for any single patient with his co-morbidities and specificities.